2021
DOI: 10.1126/sciadv.abg1448
|View full text |Cite
|
Sign up to set email alerts
|

Programmable two-dimensional nanocrystals assembled from POSS-containing peptoids as efficient artificial light-harvesting systems

Abstract: Inspired by the formation of hierarchically structured natural biominerals (e.g., bone and tooth), various sequence-defined polymers have been synthesized and exploited for design and synthesis of functional hybrid materials. Here, we synthesized a series of organic-inorganic hybrid peptoids by using polyhedral oligomeric silsesquioxane (POSS) nanoclusters as side chains at a variety of backbone locations. We further demonstrated the use of these hybrid peptoids as sequence-defined building blocks to assemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Compared to peptides, peptoids can be easily synthesized to achieve a greater side chain diversity while exhibiting much higher chemical and thermal stabilities 15 22 . Our recent work has shown that tuning amphiphilic peptoids can lead to the formation of hierarchically structured crystalline nanomaterials 17 , 18 , 23 28 , including membrane-mimetic 2D nanosheets 15 , 23 , 29 and nanotubes 16 , 25 , 28 . These peptoid-based nanomaterials are highly stable in various pH conditions and at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to peptides, peptoids can be easily synthesized to achieve a greater side chain diversity while exhibiting much higher chemical and thermal stabilities 15 22 . Our recent work has shown that tuning amphiphilic peptoids can lead to the formation of hierarchically structured crystalline nanomaterials 17 , 18 , 23 28 , including membrane-mimetic 2D nanosheets 15 , 23 , 29 and nanotubes 16 , 25 , 28 . These peptoid-based nanomaterials are highly stable in various pH conditions and at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…One of the critical hurdles for developing biomimetic hierarchical materials for wide applications is the inability to exquisitely control the processes of molecular assembly of the sequence-defined polymer building blocks. In contrast to the formation approach relying on the interface-assisted compression of monolayers (Section ), the solution crystallization approach offers some distinct advantages in the self-assembly of nanomaterials with hierarchical structures including free-standing 2D ultrathin nanomaterials, such as the high tunability in kinetic process and structure of assembly, large scale production of anisotropic nanostructures, and facile ways to control morphology by varying the solvent and/or solvophobic blocks. ,, By a cooperative interplay of multiple, weak noncovalent interactions, amphiphilic sequence-defined peptoids can self-assemble in solution through a crystallization process and result in a complex and ordered structure. This solution crystallization-triggered self-assembly processes are typically achieved by dissolving amphiphilic peptoids in a mixture of water and organic solvent, where the evaporation of organic solvents assists the self-assembly process .…”
Section: Hierarchical Self-assembly Of Sequence-defined Synthetic Pol...mentioning
confidence: 99%
“…To the best of our knowledge, the crystallization of a precise giant molecule chain was rarely investigated in the literature, and little was known about the crystal structure and formation mechanism. In spite of this, some hints can be found in the crystallization studies of molecules or polydisperse polymers that contain a certain species of giant monomers. , For example, Liu and co-workers reported screw-dislocation-induced pyramidal crystallization of POSS-based dendron-like macromolecules . The authors used a one-and-half sandwiched molecular packing model to fit the unbalanced macromolecular shape.…”
Section: Introductionmentioning
confidence: 99%